Master-Slave-Splitting Based Distributed Global Power Flow Method for Integrated Transmission and Distribution Analysis - Sun, Hongbin; Guo, Qinglai; Zhang, Boming; Guo, Ye; Li, Zhengshuo; Wang, Jianhui (IEEE transactions on smart grid, 2015)
With the recent rapid development of smart grid technology, the distribution grids become more active, and the interaction between transmission and distribution grids becomes more significant. However, in traditional power flow calculations, transmission and distribution grids are separated, which is not suitable for such future smart grids. To achieve a global unified power flow solution to support an integrated analysis for both transmission and distribution grids, we propose a global power flow (GPF) method that considers transmission and distribution grids as a whole in this paper. We construct GPF equations, and develop a master-slave-splitting (MSS) iterative method with convergence guarantee to alleviate boundary mismatches between the transmission and distribution grids. In our method, the GPF problem is split into a transmission power flow and a number of distribution power flow sub-problems, which supports on-line geographically distributed computation. Each sub-problem can be solved using a different power flow algorithm to capture the different features of transmission and distribution grids. An equivalent method is proposed to improve the convergence of the MSS-based GPF calculation for distribution grids that include loops. Numerical simulations validate the effectiveness of the proposed method, in particular when the distribution grid has loops or distributed generators.